The life of peace Philippians ; v. 2 - Lloyd-Jones, David Martyn, 1899-1981 (London, UK Hodder and Stoughton, 1990)
Contents : v. 2 : Philippians chapter 3 and 4
Keywords: Bible. N.T. Philippians III-IV -- criticism and interpretation